Geoarchaeological evaluation of ground penetrating radar and magnetometry surveys at the Iron Age burial mound Rom in Norway. Issue 4 (12th July 2017) - Schneidhofer, Petra; Nau, Erich; Leigh McGraw, Jessica; Tonning, Christer; Draganits, Erich; Gustavsen, Lars; Trinks, Immo; Filzwieser, Roland; Aldrian, Lisa; Gansum, Terje; Bill, Jan; Neubauer, Wolfgang; et al.
Abstract: Following magnetometry and ground penetrating radar surveys, a geoarchaeological field evaluation was carried out at the Iron Age burial mound of Rom in Slagendalen, Vestfold County, Norway, in order to assess the accuracy of the geophysical data interpretation and to investigate specific questions that have arisen during data interpretation. The evaluation was conducted within the framework of an archaeological excavation campaign in 2013, which enabled direct access to the subsurface materials. The archaeological stratification was recorded by laser scanning using a three‐dimensional (3D) single‐surface approach, permitting a virtual reconstruction of the excavated part of the mound and facilitating the comparison between excavation and prospection data. Selected sediment sequences were targeted with in situ and laboratory‐based measurements for correlation purposes, including magnetic susceptibility, electrical conductivity and water content measurements. Here we present the methodological approach and the results of the geophysical prospection surveys, followed by a geoarchaeological evaluation and a discussion of the impact on the overall archaeological investigation.